Invariance principle for the least squares estimates - Koval', T. L. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The weak convergence of random fields, constructed in terms of the least squares estimator of the regression coefficient of a random field (which is a two-parametric martingale difference), is established.